Металлические изделия (кельты и серпы) и генезис исторической общности КРШК эпохи раннего гальштата Карпатско-Днестровского региона - Романчук, А. (Материалы по археологии Северного Причерноморья, 2009)
Тhе article is dedicated to the topic ofthe genesis ofCISP (Cultures with Incised and Stamped ornamentation of Pottery) community. Тhе author gives some new arguments for the "ReutDniester" hypothesis, which was developed Ьу him eight years ago. Не puts the main accent on the considering ofmetal works ("kelt"-axes and sickles). Не shows that the "VyrЬitsa's types" of "kelt"-axes which spread from the Lower Danube to the Carpathian-Dniester region during the Early Hallstatt, were not related with any culture ofCISP community. Тhese types of"kelt"-axes were brought to the Carpathian-Dniester region Ьу ancestors of Кishinev-Korlateni Culture (i.e. the culture with the cannelure ornamentation ofpottery). ln the contrary, the people of the Holercani-Hansca and the Balta Cultures of CISP's community had used the "Kardashinka type" and the "Zavadovka type" (i.e., the North-Pontic types) of "kelt" -axes only.